6 - Les imaginaires populaires de la femme âgée face aux accusations de sorcellerie en République centrafricaine : une perspective genrée - Kevis Kossi, Narcisse Landry (Journal of Higher Education in Africa, 2022)
Since its irruption into the vocabulary of the social sciences, gender has not ceased to give rise to numerous reflections, publications, colloquia, etc. by researchers, particularly those at the University of Bangui. In fact, in the social representation systems of most Central African ethnic groups, the relationship between men and women is strongly influenced by socio-cultural constraints, rooted in patriarchy. As a result, women have become the object of a “gendered social construction” and therefore suffer the consequences flowing from it. In this same socio-anthropological perspective, elderly and infertile women are subjected to violence due to accusations of witchcraft. These imaginary and stereotyped facts constitute a real departure from feminist ideology, as defended and conveyed by the social sciences. In the past, elderly women were venerated and respected because of the powers they possessed, unlike the mistreated elderly women in the West. Based on an ethnographic approach and a qualitative analysis, this article aims to question the dangers of perceptions related to elderly women. The aim is to highlight the representations contained in the subconscious of the population, linked to elderly women in the Central African Republic in the era of «modernity». The study is based on direct observation of the environment. In addition to factual observation, empirical data was collected through semi-directive and free interviews with elderly women and resource persons.